2022
DOI: 10.3390/microorganisms10071331
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin, a Potent Neuroprotective Vitamin: Focus on Flavivirus and Alphavirus Proteases

Abstract: Several neurotropic viruses are members of the flavivirus and alphavirus families. Infections caused by these viruses may cause long-term neurological sequelae in humans. The continuous emergence of infections caused by viruses around the world, such as the chikungunya virus (CHIKV) (Alphavirus genus), the zika virus (ZIKV) and the yellow fever virus (YFV) (both of the Flavivirus genus), warrants the development of new strategies to combat them. Our study demonstrates the inhibitory potential of the water-solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The codon-optimised cDNA encoding CHIKV nsP2 pro (GenBank Protein Accession number AAN05101.1, strain S27-African prototype) was cloned, expressed and purified as described previously [38,77].…”
Section: Cloning Expression and Purification Of Chikv Nsp2 Promentioning
confidence: 99%
See 1 more Smart Citation
“…The codon-optimised cDNA encoding CHIKV nsP2 pro (GenBank Protein Accession number AAN05101.1, strain S27-African prototype) was cloned, expressed and purified as described previously [38,77].…”
Section: Cloning Expression and Purification Of Chikv Nsp2 Promentioning
confidence: 99%
“…The CHIKV nsP2 protease activity assay was performed as described previously [38,77], using DABCYL-Arg-Ala-Gly-Gly-Tyr-Ile-Phe-Ser-EDANS (BACHEM, Bubendorf, Switzerland) as substrate. The inhibition assay was performed in Corning 96-well plates (Merck, Darmstadt, Germany).…”
Section: Viral Protease Inhibition Assaymentioning
confidence: 99%
“… 33 Recent studies have also confirmed that riboflavin availability enhances MAIT cell protective responses to influenza A virus infections in mice 34 and inhibits entry of flaviviruses. 35 Herpesviruses establish a primary infection in the skin, lungs, orofacial, and genital mucosa, at sites colonized by MR1 ligand producing bacteria and monitored by immune cell populations including MAIT cells. During primary lytic infection, virally induced disruptions at these barrier sites could increase MR1 antigen availability, driving the early activation arm of resident MAIT cells, with consequent TCR-mediated cytolysis of virally infected host cells.…”
Section: Introductionmentioning
confidence: 99%